El debate sobre la VARD en desastres naturales. Nuevos conceptos: la gestión de riesgos - Izquierdo Carballo, María Jesús (Revista Española de Desarrollo y Cooperación, 2023)
The debate on the link between relief-rehabilitation and development (LRRD) has been focussed on the explanation of the coordination between different tools and their methodological settings, more than in making proposals for building more secure and sustainable options for development. This article deals with disaster risk management as an integrated approach, and how it should be included not only in development policies, plans and programmes, but also in humanitarian action.